The Role of the Good Agricultural Practices (GAP) Program in Enhancing the Income of Maize Farmers in Tilongkabila District - Saleh, Yanti; Mustafa, Ramlan; Dondo, Dwi Kurniawan (STIE Amkop Makassar, 2026)
Indonesia, as an agrarian country, has great potential in the development of maize as an important commodity for food, animal feed, and industrial raw materials. However, maize productivity in various regions still faces several challenges, including land degradation, climate change, and pest and disease attacks. To address these issues, the government has introduced Good Agricultural Practices (GAP) as guidelines for sustainable cultivation aimed at improving productivity and farmers’ income. This study aims to analyze the role of the GAP program in increasing the income of maize farmers in Tilongkabila District, Bone Bolango Regency. The research employed a quantitative approach using a survey method. The sample was selected purposively and consisted of 30 maize farmers who had implemented GAP for more than one planting season. Data were collected through observation, questionnaire-based interviews, and documentation, and were analyzed using a Likert scale to assess the role of GAP in terms of production, cost efficiency, and the quality and selling price of harvested maize. The results indicate that the GAP program plays a very significant role in increasing production yields with a score of 83.3%, contributes to production cost efficiency at 79.5%, and has a very strong role in improving product quality and selling prices with a score of 82.4%. These findings demonstrate that the implementation of GAP provides a tangible contribution to increasing maize farmers’ income through higher productivity, cost savings, and improved crop quality.